Pemulihan Diri Kaum Perempuan Melalui Pemuridan Dan Konseling - Panjaitan, Tutur; Nugraheni, Tisa Indah (Sekolah Tinggi Teologi Injili Indonesia Palu, 2025)
The increase in the number of women in quantity has been followed by the voice of equality and equality of gender rights. In various fields of work women have taken part and gained trust. However, it turns out that discrimination against women is not over. Therefore, self-restoration is needed in relation to the process of recovering from the inner wounds that afflict people, by the guidance of the Spirit of God. Bethany Church Magelang offers discipleship and counseling as a help actions. How much influence does discipleship and counseling simultaneously have on self-recovery? The purpose of this research is to measure the influence of discipleship and counseling simultaneously on self-recovery. The quantitative method was used in this research, the population of the female congregation in Bethany Church Magelang amounted to 150 people, the sample was determined to be 30% of 150, namely a total of 45 congregational members. At the end of the study, it was found that the effect of simultaneous discipleship and counseling on self-recovery was 60.7% (moderate).